Numerical Investigation of Bearing Capacity of Centrally and Eccentrically Loaded Surface Footing on Sand-Clay with Void Using Plaxis 2D - Abdelhakim Nezari; Rafik Boufarh; Tarek Mansouri (The Journal of Engineering and Exact Sciences)
The presence of voids under footings can significantly reduce the stability of the foundation and the superstructure above it. Estimating the bearing capacity of a footing with voids below it is a complex and challenging problem in geotechnical engineering. This study investigates the stability of centrally and eccentrically loaded surface footings supported by sand layers of variable thickness overlying clay layers, with circular voids below the center of the footing. Using the Plaxis finite element software, the influence of various parameters on the overall performance of the footing, including load eccentricity, void location, void size, and introducing geogrid reinforcement at the sand-clay interface are analyzed. The results show that increasing the void depth, add a thick layer of sand or introducing geogrid reinforcement can mitigate the impact of a void beneath a foundation.